Hong Kong, China : Growth, Structural Change, and Economic Stability During the Transition - Mihaljek, Dubravko (Occasional Papers; Occasional Paper ;, 1997)
This paper provides a detailed account of Hong Kong on the eve of its reintegration into China as a special administrative region. It analyzes recent economic development and provides a clear overview of Hong Kong's economic, financial, institutional, and political circumstances, as well a brief look at its history over the last hundred years. It suggests the changes the economy will undergo in the transition process and what it can expect in the future.